Modeliing Solution Environments for MPEC: GAMS & MATLAB - Ferris, Michael C.; Dirkse, Steven P. (My University, 1998)
We describe several new tools for modeling MPEC problems that are built around the introduction of an MPEC model type into the GAMS language. We develop subroutines that allow such models to be communicated directly to MPEC solvers. This library of interface routines, written in the C language, provides algorithmic developers with access to relevant problem data, including for example, function and Jacobian evaluations. A MATLAB interface to the GAMS MPEC model type has been designed using the interface routines. Existing MPEC models from the literature have been written in GAMS, and computational results are given that were obtained using all the tools described.
Keywords: modeling; MPEC; algorithm; complementarity